Guillain-Barré Syndrome After High-Dose Influenza Vaccine Administration in the United States, 2018–2019 Season. (2nd November 2020) - Perez-Vilar, Silvia; Hu, Mao; Weintraub, Eric; Arya, Deepa; Lufkin, Bradley; Myers, Tanya; Woo, Emily Jane; Lo, An-Chi; Chu, Steve; Swarr, Madeline; Liao, Jiemin; Wernecke, Michael; et al.
Abstract: Background: The Vaccine Safety Datalink (VSD) identified a statistical signal for an increased risk of Guillain-Barré syndrome (GBS) in days 1–42 after 2018–2019 high-dose influenza vaccine (IIV3-HD) administration. We evaluated the signal using Medicare. Methods: We conducted early- and end-of-season claims-based self-controlled risk interval analyses among Medicare beneficiaries ages ≥65 years, using days 8–21 and 1–42 postvaccination as risk windows and days 43–84 as control window. The VSD conducted chart-confirmed analyses. Results: Among 7 453 690 IIV3-HD vaccinations, we did not detect a statistically significant increased GBS risk for either the 8- to 21-day (odds ratio [OR], 1.85; 95% confidence interval [CI], 0.99–3.44) or 1- to 42-day (OR, 1.31; 95% CI, 0.78–2.18) risk windows. The findings from the end-of-season analyses were fully consistent with the early-season analyses for both the 8- to 21-day (OR, 1.64; 95% CI, 0.92–2.91) and 1- to 42-day (OR, 1.12; 95% CI, 0.70–1.79) risk windows. The VSD's chart-confirmed analysis, involving 646 996 IIV3-HD vaccinations, with 1 case each in the risk and control windows, yielded a relative risk of 1.00 (95% CI, 0.06–15.99). Conclusions: The Medicare analyses did not exclude an association between IIV3-HD and GBS, but it determined that, if such a risk existed, it was similar in magnitude to prior seasons. Chart-confirmed VSD results did not confirm an increased risk of GBS. Abstract : Using VSD and Medicare data, we rapidly evaluated a potential association between the 2018–2019 high-dose influenza vaccine and GBS and determined that, if a risk existed, it was similar in magnitude to that from prior seasons.